Population pharmacokinetics of efpeglenatide in individuals with obesity and with type 2 diabetes - Choi, Seungchan; Seo, Jiyoung; Park, Suemin; Kim, Na Young; Kim, Hyeeun; Lim, Hyeong-Seok (Frontiers in Pharmacology, 2025)
BackgroundEfpeglenatide (HM11260C) is a long-acting GLP-1 receptor agonist under development for obesity. A population pharmacokinetic (PK) analysis was conducted to characterize its PK properties and evaluate covariate effects to support clinical dosing strategies.MethodsPooled PK data from six clinical studies in participants with type 2 diabetes or obesity were analyzed using nonlinear mixed-effects modeling (NONMEM). Covariate effects, model diagnostics, and simulations were used to assess exposure and dosing strategies.ResultsA two-compartment model with dual absorption pathways adequately described the data. Body weight and disease status influenced absorption and clearance; however, predicted exposure differences across weight percentiles and demographic subgroups were modest and within conventional bioequivalence limits. Simulations suggested approximately dose-proportional increases across the evaluated dose range with once-weekly administration and supported the feasibility of stepwise dose-escalation.ConclusionEfpeglenatide PK was well characterized across type 2 diabetes and obesity populations. Although some covariates affected PK parameters, their impact on exposure was not clinically meaningful. These results support a uniform dosing strategy without routine dose adjustment and provide quantitative evidence for stepwise dose escalation in ongoing clinical development for obesity.